2017
DOI: 10.1371/journal.pone.0179836
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in lens parameters measured by ocular biometry in a cataract surgery population

Abstract: PurposeTo investigate whether differences exist in lens position and other lens parameters among major ethnic groups with cataractous eyes, which may help explain racial differences in angle closure risk.MethodsThis retrospective, cross-sectional study included 807 adult patients who had cataract surgery between years 2014 and 2016 at the University of California, San Francisco (UCSF). Adult patients of white, Asian, Hispanic and African-American ethnicity were included. Lens position (LP), defined as anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 45 publications
4
40
2
Order By: Relevance
“…In the study among black south Africans, the mean LT was 3.69 (± 0.25) mm while a study comparing ethnic differences in lens parameters found the average measurements in whites 4.52 (0.46) mm, African American 4.48 (±0.54) mm, Asians 4.60 (±0.46) mm, and Hispanics 4.53 (±0.44) mm. 21 In our study, age, height, and BMI have a significant association in the univariable analysis but only age ( p -value <0.001) persisted after adjustment. This is in keeping with other studies.…”
Section: Discussioncontrasting
confidence: 41%
“…In the study among black south Africans, the mean LT was 3.69 (± 0.25) mm while a study comparing ethnic differences in lens parameters found the average measurements in whites 4.52 (0.46) mm, African American 4.48 (±0.54) mm, Asians 4.60 (±0.46) mm, and Hispanics 4.53 (±0.44) mm. 21 In our study, age, height, and BMI have a significant association in the univariable analysis but only age ( p -value <0.001) persisted after adjustment. This is in keeping with other studies.…”
Section: Discussioncontrasting
confidence: 41%
“…The thickness of the crystalline lens varies depending on age and race [10, 11], so measured axial length values in the same eye may differ between measurements made using the individual refractive indices and those made using the equivalent refractive index; the error of the intraocular lens (IOL) power calculation may also show discrepancy between the two biometers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the wide prevalence of cataract and cataract–related blindness in developing countries and, specifically, in Iran ( 19 ), and with a rapidly aging population, this problem is predicted to multiply in future. The ethnic differences in ocular parameters have suggested that the surgical outcome of cataract surgery may be different in different ethnicities/races ( 20 , 21 ), while to the best of our knowledge, there are few studies in our country investigating the post-operative complications of cataract surgery ( 22 ). Considering the increased cataract surgical rate in our country from about 2.5 times from 526 to 1,331 per million over five years (2000–2005) ( 23 ), it is necessary to determine the surgical outcome of cataract surgery in Iranian patients.…”
Section: Introductionmentioning
confidence: 99%